Boron-terminated diamond (100) surfaces with promising structural and electronic properties. Issue 15 (2nd April 2020) - Sun, Zhaolong; Yang, Mingchao; Wang, Xueting; Wang, Peng; Zhang, Chunling; Gao, Nan; Li, Hongdong
Abstract : Boron coverages on diamond (100) surfaces with varying configurations show novel electron affinity property. Abstract : Boron (B) termination plays an important role in determining the surface properties of the diamond (100) surface. A recent study [ J. Mater. Chem. C, 2019, 7, 9756] reported a stable surface structure with one B atom per carbon atom based on high-symmetry adsorption sites having a negative electron affinity (EA) property. In this work, using the global structure prediction method and first-principle calculations, four kinds of B-diamond (100) surfaces with 0.5 monolayers (0.5 ML, one B atom per two carbon atoms), and 1 ML-α, 1 ML-β, and 1 ML-γ (one B atom per carbon atom with three types of configurations known as α, β, and γ) coverages obtained are dynamically and thermally stable. The calculations reveal that B termination effectively modulates the EA of the diamond (100) surface. The 0.5 ML coverage has a small positive EA of 0.24 eV, while the latter three 1 ML coverages with different configurations possess the negative EA of −1.27, −1.25, and −0.76 eV, respectively, due to the difference in charge accumulation and surface dipole moment. Moreover, the B-related surface states are introduced into the bandgap of the bulk diamond, and the band dispersions of the surface states are small (large) in 0.5 ML and 1 ML-γ (1 ML-α and 1 ML-β) as a consequence of the different arrangements of B atoms and the bond lengths between B atoms on the surface. Our finding provides theoretical guidance for the design and fabrication of B-diamond-based electronic devices.